2018
DOI: 10.1007/s11605-018-3857-z
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pneumonia is Associated with Long-Term Oncologic Outcomes of Definitive Chemoradiotherapy Followed by Salvage Esophagectomy for Esophageal Cancer

Abstract: The present study demonstrates the long-term outcomes and risk factors for mortality of salvage esophagectomy. To improve OS after salvage surgery, the development of a means of decreasing pulmonary complications is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…13 Several studies identify postoperative pneumonia as a predictor of short-term and long-term mortality after surgery. [14][15][16][17][18][19] Is there a difference in the outcomes of postoperative pneumonia between patients with and without T2DM?…”
Section: Introductionmentioning
confidence: 99%
“…13 Several studies identify postoperative pneumonia as a predictor of short-term and long-term mortality after surgery. [14][15][16][17][18][19] Is there a difference in the outcomes of postoperative pneumonia between patients with and without T2DM?…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicate that complications might lead to death from other diseases in the long term. Takeuchi et al [21] investigated the prognosis of 49 patients who underwent salvage esophagectomy. They reported that 9 (56%) of 16 patients with postoperative pneumonia after salvage esophagectomy died from illnesses unrelated to esophageal cancer over the long term.…”
Section: Discussionmentioning
confidence: 99%
“…These two results are consistent with our result that deaths from other diseases were more [20] stated that low albumin level, high C-reactive protein level, clinical node positivity, and operative blood loss are associated with the occurrence of postoperative complications. Hayami et al [21] reported that low BMI, poor performance status, and high radiation dose are associated with Overall survival (OS) curves by postoperative complication status, pulmonary complication status, and anastomotic leakage status. a Survival of patients with complications was significantly poorer than survival of patients without complications (HR, 2.06; p = 0.017).…”
Section: Discussionmentioning
confidence: 99%
“…47 R0 resection was performed in 42.4%-86.9% of cases. [18][19][20][21][22][23][24][25][26][27][28][29][33][34][35][36][37][38][39][40][41]44,46 One-year, 3-year, and 5-year OS rates were 45.7%-84%, 18,27,34,[36][37][38]40,46 29.8%-63%, 18,[26][27][28]34,38,40,46 and 5.7%-51.6%, 18,26,27,[34][35][36][37]46 respectively. Multivariate analysis revealed the following independent prognostic factors: R0 resection, 21,[23][24]…”
Section: Ta B L E 1 Summary Of Studies On Esophagectomy After Dcrtmentioning
confidence: 99%